Syed Muhammad Naquib al-Attas Syed Muhammad Naquib al-Attas: Islamization of Knowledge by Developing Genuine Islamic Paradigm - Nasution, Ansor (JURNAL ISLAMIKA, 2021)
The international conference of Muslim countries on education periodically began in 1977 in Mecca al-Mukarramah, this made Muslims intensively discuss the integration of science and Islam, Syed Muhammad Naquib al-Attas was one of the figures who attended the conference. Al-Attas views that one of the causes of the decline of Muslims is because Muslims accept what knowledge from the west is and recognize the truth of science from the west, which according to al-Attas, knowledge from the west is not original science, it has been contaminated. by western culture even inserted the mission of secularism in its spread. According to al-Attas, so that Muslims can rise and develop, they must return to the original concept of science, namely knowledge that comes from the owner of knowledge, namely Allah by making the Qur'an and Hadith as a guide, which is called the Islamization of knowledge, al-Attas argues that the value-free science echoed by western thinkers is an attempt to weaken Muslims and distance Muslims from real knowledge. The steps offered by al-Attas in the process of Islamization of science are; the first by eliminating secular concepts and western culture from science, the second by incorporating Islamic concepts that are in accordance with current developments as standard terms in education. But before doing these two steps, according to al-Attas, what needs to be done first is to Islamize the language.